1986
DOI: 10.1051/jphys:019860047090155500
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear electron spin resonance study of archaebacteria lipid dynamics

Abstract: The spectral diffusion occurring in non-linear electron spin resonance experiments performed at a suitable frequency of field modulation is exploited to gain dynamical information on an unusual class of lipids extracted from bacteria living in extreme physical conditions (high temperature and very low pH). These lipids are quite different from the usual fatty acid lipids and their molecular structure seems to play a particular role in the stability of the plasma membrane of these bacteria. An accurate and exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…When using these calibration curves, it is necessary to record the ST-ESR spectra under experimental conditions equal to those reported [35]. In this connection an accurate calibration of our instrument has been already performed [28]. Figure 1 shows some representative spectra of 3Mal-HSA at varying degrees of hydration at room temperamre.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When using these calibration curves, it is necessary to record the ST-ESR spectra under experimental conditions equal to those reported [35]. In this connection an accurate calibration of our instrument has been already performed [28]. Figure 1 shows some representative spectra of 3Mal-HSA at varying degrees of hydration at room temperamre.…”
Section: Discussionmentioning
confidence: 99%
“…Spectra were acquired on a HP 86A personal computer through a home-made interface connected to an IEEE-488 bus [27]. ST-ESR expefiments were carried out in the experimental conditions reported by Bruno et aL [28].…”
Section: Esr Measurementsmentioning
confidence: 99%
“…19 The lipid lateral diffusion is also significantly reduced compared to normal lipid diffusion. 31,32 That is why, to date, the only MD studies reported have started from preassembled starting configurations with all the bolalipids in the spanning conformation, omitting the equilibration process. 33−35 To fasten the bilayer equilibration, we use the mean field force approximation (MFFA)-boundary potential method developed by Risselada et al 36 to create and maintain an artificial pore in the center of the self-assembled bilayers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Naturally-occurring bolalipids have been characterized with respect to their membrane permeability [10], capacitance [22], and lateral diffusion/correlation times [23][24][25][26], however, there are very few systematic studies of the influence of lipid structure on membrane function in synthetic bolalipid systems [9][10][11]. Studies of this type are of particular interest since they may reveal the underlying structural features that are most important for the formation of stable and fluid bolalipid membranes for supported membrane sensor applications.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14] These unique features have stimulated their use in vaccine and drug delivery systems, 5 in supported membrane devices, 13,15,16 as design elements for coupled electron/ion transport across vesicle membranes, 17,18 as paleobiological markers (i.e., molecular fossils), 19,20 and a host of other applications. 21 Naturally occurring bolalipids have been characterized with respect to their membrane permeability, 10 capacitance, 22 and lateral diffusion/correlation times; [23][24][25][26] however, there are very few systematic studies of the influence of lipid structure on membrane function in synthetic bolalipid systems. [9][10][11] Studies of this type are of particular interest since they may reveal the underlying structural features that are most important for the formation of stable and fluid bolalipid membranes for supported membrane sensor applications.…”
Section: Introductionmentioning
confidence: 99%